Neuroendoscopic Navigated One-Step Removal of Crossed Ventricular Catheter Fragments: Technical Note - Calì, Alessandro; Scalia, Gianluca; Marrone, Salvatore; Riolo, Carmelo; Vasta, Giuseppe; Umana, Giuseppe Emmanuele; Cicero, Salvatore; Iacopino, Domenico Gerardo; Nicoletti, Giovanni Federico (Journal of Pediatric Neurology, 2021)
Introduction Neuroendoscopy plays an important role in minimally invasive neurosurgery. The authors reported an interesting case of a pediatric patient with multiple ventriculoperitoneal shunt (VPS) revision surgeries, presenting with VPS infection and with two crossed intraventricular floating catheter fragments, successfully removed through a neuroendoscopic navigated one-step procedure. A literature review regarding this exceedingly rare condition has also been discussed.Case Description An 11-year-old female patient with a history of congenital hydrocephalus was admitted to the emergency department with symptoms of intracranial hypertension, psychomotor agitation, and tetraparesis. She had a history of previous multiple VPS revisions. She had an urgent brain computed tomography scan that documented hydrocephalus; the VPS's intraventricular catheter tip was sited at the level of the right frontal horn. Two small floating catheter fragments, not connected to the VPS, were identified: the first close to the right lateral ventricle at the level of the right occipital horn, the second one between the right occipital horn and the third ventricle. First, she underwent an exteriorization of the distal catheter for VPS. Cerebrospinal fluid examination documented hyperproteinorrachia and a positive culture for Staphylococcusaureus. Then a navigated right transfrontal endoscopic approach to the right lateral ventricle was performed extending to the previous burr hole and achieving a wide range of working angle with a rigid 0-degree lens endoscope. Intermittent irrigation generating convective flow was performed such as to mobilize the catheters tip gently upward, to remove them by grasping. Finally, a whole VPS replacement has been performed.Conclusion Persistence of intraventricular floating catheter fragments can lead to subacute or chronic infections. Neuroendoscopic retrieval represents a safe and effective alternative to a more extensive and invasive surgical approach. However, the exact catheter tip identification, grasping, and removal can be difficult to achieve, due to the technical instrumentation characteristics and altered intraventricular anatomy in chronic congenital hydrocephalus. In our experience, endoscopic convective flow induction through saline irrigation can determine floating intraventricular catheter fragments movement aiming to their identification and subsequent successful endoscopic retrieval.
Keywords: neuroendoscopy; shunt catheter; ventricular system; hydrocephalus; convective flow